Knowledge of antipsychotic medication and their side effects among psychiatric nurses at a tertiary hospital in Lesotho - Matete, Relebohile Paulus; Rathobei, Libuseng Moureen (New Voices in Psychology, 2023)
Factors that impede the physical health monitoring of patients with severe mental illness are multidimensional, and healthcare providers’ knowledge and expertise regarding antipsychotic medication and side effects remain key determinants of the frequency and quality of screening a patient shall be subjected to. This challenge transcends the monitoring of patients treated with antipsychotics, where scholars have determined a lack of knowledge about screening for adverse effects, resulting in poor clinical assessments among patients prescribed antipsychotics. This study aimed to describe nurses’ knowledge regarding antipsychotic medications and their side effects at the psychiatric hospital in Lesotho. To guide the research process, a quantitative, non-experimental, descriptive approach was employed with 40 nurses out of 44 nurses as respondents, who were selected using convenience sampling, and respondents rated their knowledge regarding the side effects of antipsychotic medication using a Likert scale on a structured research questionnaire. The data were collected using a self-administered questionnaire, analysed using SPSS (version 28), and displayed using tables, frequencies, standard deviations, and means. This study's female respondents comprised 30 (75.0%) and 10 (25.0%) males. The mean age was 39.05 (SD 8.9), with eight years of psychiatry experience. A total of 29 (72.0%) had sufficient antipsychotic knowledge (t = 36.38, df = 39, p < .000), 31 (78.3%) and had adequate knowledge of the side effects of antipsychotic drugs (t = 34.00375, df = 39, p < .000). In conclusion, this study reveals a positive trend in nursing knowledge about antipsychotic medications and associated side effects, highlighting the importance of ongoing professional development to maintain and enhance this expertise.